UJI KADAR SAKARIN PADA MINUMAN RINGAN BERMEREK YANG BEREDAR DI KOTA PEKANBARU - Karolina Rosmiati (Akademi Kesehatan John Paul II Pekanbaru, 2018)
Food addtives plays an important role in the production of beverages to improve the quality, taste and shelf life of beverages products significantly. Saccharin is widely used as artificial sweetener in soft drinks manufacturing industries, including branded soft drinks with plastic packaging. The purpose of this research was to determine the levels of saccharin in branded soft drinks with plastic packaging sold at Pasar Kodim Pekanbaru. The samples were collected by purposive random sampling. five samples were analyzed by qualitative test using resorcinol reagent and quantitative test with alkalimetric titration methods. The qualitative test showed that all samples were positive for saccharin indicated by the changes of color turning green fluorescence. The level of saccharin in the samples ranged between 160 – 580 mg/kg of ingredients. The higest levels of saccharin (580 mg/kg) was assayed in sample E, and the smallest level ( 160 mg/kg)was assayed in sample B and C. According to Permenkes no.722/Menkes/Per/IX/1988 concerning food additives, maximal saccharin levels allowed in soft drink was 300 mg/kg of ingredients or 5 mg/kg of body weight. Only one sample (sample E) exceeded the limit of maximal saccharin levels allowed in soft drink. Samples A, B, C, dan D that had been tested could be considered as safe to be consumed, but the daily intake should be in caution.